(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Attendance is very important task for an organization like school, colleges, companies etc. Taking of attendance manually is very time consuming. It takes up to 5 to 20 minutes and it depends upon the number of students in a class. Now a day’s technology become more advance, so we have to use biometric system for attendance because it takes very less time as compared to taking attendance manually. In this project we are going to make an attendance system using face recognition. There are many algorithms by which we can make an attendance system using face recognition. In this project we use Viola-Jones Algorithm and Local Binary Pattern Histogram (LBPH) Algorithm. Viola-Jones algorithm is used for face detection and Local Binary Pattern Histogram is used for samples training and face recognition